2017
DOI: 10.1111/eci.12840
|View full text |Cite
|
Sign up to set email alerts
|

Polypoidal choroidal vasculopathy treatment options: A meta‐analysis

Abstract: BackgroundCombined treatment with intravitreal anti‐vascular endothelial growth factor (anti‐VEGF) and verteporfin photodynamic therapy (PDT) is widely used for patients with polypoidal choroidal vasculopathy (PCV), although clinical evidence regarding the therapeutic efficacy and safety of such treatment remains lacking.Design/MethodsWe performed a meta‐analysis of previously reported studies comparing combination treatment, PDT monotherapy, and anti‐VEGF monotherapy. Primary outcome measures included changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…These are humanized monoclonal antibodies which act to decrease elevated VEGF at the site of neovascularization, eventually restoring retinal thickness and function (Golbaz et al, 2011). Other interventions for wet AMD include verteporfin photodynamic therapy, which is used in combination with anti-VEGF therapy to stimulate polyp regression in PCV (Cho et al, 2012; Qian et al, 2018). While anti-VEGF therapy has restored vision for many, the monotherapy does not improve visual acuity in a substantial number of AMD patients as a form of long-term management (Rofagha et al, 2013; Fernández-Robredo et al, 2014; Bracha et al, 2017; Dunn et al, 2017; Jaffe et al, 2017; Malek et al, 2018).…”
Section: Vascular Etiology In Age-related Macular Degenerationmentioning
confidence: 99%
“…These are humanized monoclonal antibodies which act to decrease elevated VEGF at the site of neovascularization, eventually restoring retinal thickness and function (Golbaz et al, 2011). Other interventions for wet AMD include verteporfin photodynamic therapy, which is used in combination with anti-VEGF therapy to stimulate polyp regression in PCV (Cho et al, 2012; Qian et al, 2018). While anti-VEGF therapy has restored vision for many, the monotherapy does not improve visual acuity in a substantial number of AMD patients as a form of long-term management (Rofagha et al, 2013; Fernández-Robredo et al, 2014; Bracha et al, 2017; Dunn et al, 2017; Jaffe et al, 2017; Malek et al, 2018).…”
Section: Vascular Etiology In Age-related Macular Degenerationmentioning
confidence: 99%
“…Two systematic reviews and meta-analysis[214215] suggested that combination of PDT and anti-VEGF therapy had more potential in achieving early and maintaining better long-term visual outcomes than PDT monotherapy. Additional PDT sessions induce SRH and ischemic damage to choroidal tissue, explaining the loss of improvement in VA in the PDT monotherapy.…”
Section: Combination Therapymentioning
confidence: 99%
“…Synthesized evidence from 4 studies was published before 2019 19 22 , and the latest meta-analysis derived conclusions from heterogeneous findings due to mixed data from retrospective studies and 2 RCTs. Notably, conceptual heterogeneity is unavoidable Consequently, the appropriate treatment strategy for PCV remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in early combination therapy, a patient receives PDT and anti-VEGF therapy at the beginning of the treatment course. However, in late combination therapy, patients receive anti-VEGF first, followed by rescue PDT.Synthesized evidence from 4 studies was published before 2019 [19][20][21][22] , and the latest meta-analysis derived conclusions from heterogeneous findings due to mixed data from retrospective studies and 2 RCTs. Notably,…”
mentioning
confidence: 99%